Millenarianism and the Narration of the Nation: Narratives about the Korpela Movement - Heith, Anne (Umeå University Library, 2009)
The Korpela movement was a millenarian movement which emerged in Northern Sweden in the nineteen-thirties. The article explores the use of historical subject matter about the movement in newspaper journalism, literary writing, and in the branding of Toivo Korpela and the Korpela movement on the World Wide Web in the context of present-day marketing of attractions for visitors. The argument of this article is that the literary writings of Henning and Ernst Sjöström and Bengt Pohjanen respectively represent two conflicting ways of narrating the Swedish nation. The Sjöström brothers’ novel Silverarken [‘The silver ark’] represents a nationalist pedagogy in which the narrative of the nation exemplifies a teleology of progress. This mode of narrating is problemized by a double narrative movement which includes a “‘timeless’ discourse of irrationality” (Bhabha), exemplified in a number of Bengt Pohjanen’s novels, which destabilizes and deconstructs the narration of the nation as a story about homogeneity and linear progress. This latter mode of narrating makes visible the split in the narration of the nation between the progressive, accumulative temporality of the modern Swedish welfare state and the performative subversion of an alternative logic which is also claimed to be representative.